The tale of two bad mice. - Potter, Beatrix, 1866-1943. (New York : F. Warne & Co., Inc., 1932)
Two little mice, Tom Thumb and Hunca Munca, get into some mischief in the dollhouse while the rightful occupants are out for a buggy ride.
K-3
3.7
Keywords: Mice -- Fiction